Math, asked by deekshitha1923, 4 months ago

if log 2 to the base x+ log 8 the base x+ log 64 to the base xequal to 3 then x

Answers

Answered by mathdude500
2

\large\underline{\sf{Solution-}}

Given that

\rm :\longmapsto\: log_{x}(2) +  log_{x}(8) +  log_{x}(64) = 3

\rm \:  \:  \rm :\longmapsto\:\:  \:  log_{x}(2 \times 8 \times 64)  = 3

 \:  \:  \:  \:  \: \red{\bigg \{ \because \: log_{a}(x) +  log_{a}(y)=log_{a}(xy)\bigg \}}

\rm \:  \:  \rm :\longmapsto\:  \:  \:  log_{x}(2 \times  {2}^{3} \times  {2}^{6})  = 3

\rm \:  \:  \rm :\longmapsto\: \:  \:  log_{x}( {2}^{1 + 3 + 6} )  = 3

 \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \red{\bigg \{ \because \:  {a}^{x}  \times  {a}^{y}  =  {a}^{x + y} \bigg \}}

\rm \:  \:  \rm :\longmapsto\:  \:  \:  log_{x}( {2}^{10} )  = 3

\rm :\longmapsto\: {2}^{10} =  {x}^{3}

 \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \red{\bigg \{ \because \: log_{x}(y) = z \: then \: y =  {x}^{z}   \bigg \}}

\rm :\longmapsto\: {x}^{3}  =  {2}^{9}  \times 2

\bf\implies \:x =  {2}^{3} \times  {2}^{ \frac{1}{3} }

\bf\implies \:x = 8 \:  \sqrt[3]{2}

Additional Information :-

\boxed{ \sf \: log_{x}(x)  = 1 }

\boxed{ \sf \: log_{x}(y)  = \dfrac{1}{ log_{y}(x) }  }

\boxed{ \sf \:  {a}^{ log_{a}(x) } = x }

\boxed{ \sf \:  {a}^{ ylog_{a}(x) } =  {x}^{y}  }

\boxed{ \sf \:  log(1) = 0 }

\boxed{ \sf \:  {e}^{ log_{e}(x) }  = x}

Similar questions